Efeito da fração do ejaculado e do método de conservação sobre as características físicas do sêmen suino e a fertilidade de fêmeas - Diego Vilela Alkmin (2010)
The effect of two boar ejaculate fractions, first portion 15ml of the rich fraction (F1) and the remaining fraction (F2), submitted to two semen conservation methods (dilution in MR-A T1 or in glycine-egg-yolk - GGO T2 and kept at 17° or 5°C, respectively) was evaluated on the physical and morphological characteristics of the semen stored in special container, at different times (experiment I) as well on the fertility and prolificity of sows (experiment II). In the first experiment, the evaluations were made in fresh semen as well immediately after its dilution, and at 12, 24, 36, 48, and 72h of storage inside special container. F2 sperm cells diluted in GGO and cooled at 5ºC resulted in higher values of motility, although influence of the fraction was not observed on the percent of normal cells. Spermatic morphology was kept inside the acceptable thresholds in all treatments throughout storage. In experiment II, neither effect of fraction nor semen conservation method on the fertility and prolificity were observed. Thus, due to low volume and high concentration, F1 seems to be more adequate to transportation, while the remaining of the ejaculate (F2), considering the opposite features, could be efficiently used inside the hog farm itself